Peluang Inovasi Kelembagaan Pesantren Berbasis UU Nomor 18 Tahun 2019 - Abdul Khalim,; Supriadi, Dedi (Diversity: Jurnal Ilmiah Pascasarjana, 2024)
The aim of this research is to obtain opportunities for Islamic boarding school innovation from Law Number 18 of 2019. The research method uses qualitative methods, namely examining the text of the law, educational innovation books and relevant journals. The research results obtained are (1) Innovation opportunities for Islamic boarding school institutional units. In accordance with article 5 paragraphs 1a, 1b and 1c. There are the Buku Kuning Islamic boarding schools, Dirasah Islamiah or Muallimin Islamic boarding schools and other forms of Islamic boarding schools that are integrated with General Education. (2) Opportunities for innovation in combining Islamic boarding schools with universities from article 22 paragraph 1 and paragraph 7. Islamic boarding schools are combined with universities or Islamic boarding school-based colleges. (3) Opportunities for innovation in combining Islamic boarding schools with vocational training centers. The basis is article 19 paragraph 2b, article 21 paragraph 2b and article 23 paragraph 4. At a minimum, Islamic boarding school graduates must have work skills to be accepted for work. (4) Opportunities for establishing a community service division which has been mandated in article 45. (5) Opportunities for establishing a masayikh council tasked with ensuring the quality of Islamic boarding schools. This task is regulated in article 27 paragraphs 1, 2, 3a, 3b, 3c, 3d and 3e. (6) The opportunity for institutions to receive financial assistance from the government is greater as explained in articles 48 and 49.